Effect of sodium hexametaphosphate on the flotation separation of biotite and K-feldspar in the NaOL/DDA system - Xingyu Hu; Bo Mei; Lingfeng Shen; Wei Sun; Yanxiu Wang; Jinghua Huang; Li Wang (Minerals Engineering, 2026)

Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Distinct soil microbial community composition and structure: evidence from soil inside and outside the cattle farm - Qi Ding; Jiayi Li; Fengling Xue; Wenjun Cui; Shiguang Hu; Lingfeng Yu; Wanyue Huang; Lin Li; Ping Cheng (Brazilian Journal of Microbiology, 2026)

Largemouth bass virus infection subverts immune-redox homeostasis in zebrafish and is associated with coordinated suppression of NF-κB and Nrf2 signaling - Lingfeng Guan; Xinyue Zhang; Ting Yu; Yang Liu; Jiamei Long; Runchang Zhou; Hua Huang; Jinglin Tan; Zhifeng Chen; Qiwei Qin; Shaowen Wang (Fish & Shellfish Immunology, 2026)

Topology-engineered hydrogel with cellulose nanosheets for robust and high-capacity zinc-ion batteries - Wenxuan Lei; Heng Huang; Wenyu Liu; Lingfeng Zhou; Guoping Li; Pan Chen; Zu Chang; Jiangfeng Qian; Ang Lu (Carbohydrate Polymers, 2026)

Integrating machine learning and deep learning with multiple molecular fingerprints for topoisomerase I inhibitor screening and lead identification - Huang Zeng; Xuerou Zheng; Jiayao Liu; Shengyuan Zhang; Hua Nie; Nan Wang; Lingfeng Wu; Chunfang Liu; Ming Zhai; Hao Yang; Jiunlong Yang; Bo Qiu (Molecular Diversity, 2026)

Intensive mariculture promotes molecular reorganization of dissolved organic matter in coastal waters - Kai Shen; Niangming Duan; Zhibing Jiang; Jiang Shen; Haibo Jiang; Hailong Huang; Lingfeng Zhou; Dongping Shi; Mei Li; Ying Kang; Yuanhao Wang; Xubiao Yu (Environmental Research, 2026)

Nonclassical modes of subtropical Indian Ocean dipole identified by autoencoder and their distinct climatic impacts - Bicheng Huang; Lingfeng Zheng; Zengping Zhang; Tao Su; Guolin Feng; Zhonghua Qian; Yongping Wu (Climate Dynamics, 2026)

Nutrient-acquisition and -utilization strategies of seagrasses in oligotrophic environments - Lin Wu; Jianguo Du; Lingfeng Huang; Hongtao Zhong (Frontiers in Marine Science, 2026)
Seagrass meadows rank among the most productive coastal ecosystems, yet our understanding of their nutrient-acquisition strategies in oligotrophic environments remain fragmented. Current research tends to focus on isolated processes, such as leaf or root uptake, without adequately integrating morpho-physiological traits, sediment heterogeneity, or microbial interactions. This fragmentation constrains our ability to predict seagrass responses to global environmental change. This review synthesizes seagrass nutritional ecology and shows that species in oligotrophic systems employ complementary strategies, including high-affinity foliar absorption, extensive root proliferation, and internal resorption. Crucially, these traits exhibit high plasticity and are modulated by intricate plant-microbe mutualisms, such as nitrogen fixation and phosphorus solubilization. We further demonstrate how sediment properties and hydrodynamic create spatial heterogeneity that dictates site-specific nutrient bioavailability. We propose three priority research directions: (1) deciphering the genetic and epigenetic drivers of phenotypic plasticity adaptation to oligotrophy; (2) applying stable isotope tracers and comparative genomics to quantify the net functional benefits of the seagrass microbiome; and (3) assessing long-term impacts of synergistic stressors (e.g., warming and eutrophication) on meadow structure and biogeochemical functions. By treating oligotrophic environments as natural laboratories, this review informs restoration efforts and the need to safeguard ecosystem services globally, particularly blue carbon sequestration and biodiversity conservation.

An ecosystem-based evaluation of the carrying capacity ratio for bivalve and macroalgae polyculture: a case study in Sansha Bay, China - Wen Ma; Bin Xie; Cheng Huang; Nianxi Chen; Lingfeng Huang (Journal of Environmental Management, 2026)

Modelling and operation performance of the hybrid borehole heat exchangers constituted of a shallow U-pipe array and medium-deep coaxial pipe - Shilong Yang; Yaru Li; Lingfeng Huang; Qingbo Yang; Ke Zhu; Yudong Mao; Wenke Zhang; Mingzhi Yu (Energy and Buildings, 2026)

Multiscale-reinforced high-strength MXene-based EMI shielding films with integrated electronic skin functionalities - Lingfeng Yu; Yanni Yang; Xinyu Huang; Yihao Xiao; Lishun Fu; Ruopeng Liu; Long Xia; Yahui Xue (Chemical Engineering Journal, 2026)

Community assembly and nitrogen metabolic characteristics of size-fractionated microorganisms in floating bed restoration area - Yi Shi; Rui Zhao; Lingfeng Huang; Wenjing Zhang (Journal of Oceanology and Limnology, 2026)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Plasmid engineering reveals size-dependent effects of plastic particles on horizontal gene transfer via transformation in Escherichia coli: Critical roles of plasmid size and plastic particle-bacteria spatial configuration - Lingfeng Zhu; Xuelan Chen; Zhihao Zhao; Mingzhu Huang; Yuechen Zhu; Hongtao Li; Yanna Shao; Mengrong Wang; Sicheng Xiong; Baoshan Xing (Journal of Hazardous Materials, 2025)

Effects of cold plasma treatment and xanthan gum on the longan seed starch: physicochemical, rheological and digestive properties - Rui Huang; Yitong Chen; Lingfeng Cheng; Mengzhu Shen; Yaqin Yu; Fangfang Wu; Miaomiao Shi; Yong Hu; Chao Huang; Yun Chen (Food Chemistry, 2025)

“Peak reduction and trough filling”: A promising strategy for restoring a degraded coastal lagoon from ecological imbalance to stability through integrated biomanipulation - Wen Ma; Cheng Huang; Nianxi Chen; Lingfeng Huang (Ocean & Coastal Management, 2025)

Nanomaterial-powered immunotherapy: A next-generation therapeutic paradigm for bacterial infections - Xiaotong Sun; Shengnan Huang; Tong Ye; Lingfeng Xu; Yongfang Wang; Anqi Liu; Chao Liu; Yu Han; Mengfei Pang; Xuan Wu; Xin Pang (Chemical Engineering Journal, 2025)

Effect of annealing and tea polyphenols on the physicochemical properties of mango starch - Rui Huang; Yaqin Yu; Mengzhu Shen; Lingfeng Cheng; Yitong Chen; Hongwei Wu; Fangfang Wu; Chao Huang; Yong Hu; Yun Chen (Food Bioscience, 2025)

Glyceryl lignin enhances lytic polysaccharide monooxygenase (LPMO) oxidative activity via electron transfer and H2O2 generation: Mechanistic insights from glycerol pretreatment - Lingfeng Long; Han Wang; Chong Wang; Shoushuai Feng; Hailin Yang; Xianzhi Meng; Chen Huang; Arthur J. Ragauskas (Chemical Engineering Journal, 2025)

Non-covalent bonding induced superior fire resistance of functionalized graphene oxide and carbon nanotubes paper for Joule heating and ultra-durable fire alarming - Ao Cai; Cunjiong Fang; Lingfeng Pan; Wenhua Chen; Pengju Liu; Hao Huang; Yuan Liu (Chemical Engineering Journal, 2025)

Determination of Trophic Levels of Marine Fish Using Stable Isotope Analysis of Fish Scale Nitrogen (δ15N) in the Yellow Sea and Northern East China Sea - Huaiyu Bai; Lingfeng Huang; Yao Sun (Journal of Ocean University of China, 2025)

Micropropagation and ISSR Molecular Analysis of the Endangered Species Sargassum fusiforme: A Biotechnological Approach - Nedaa Ahmed; Mohamed A. M. El-Tabakh; Hala F. Mohamed; Changan Xu; Lingfeng Huang (Journal of Ocean University of China, 2025)

Adaptation of Marine Heterotrophic Protists to Long‐Term Warming Selection - Mengwen Pang; Zuyuan Gao; Lingfeng Huang; Chuk Man Chan; Xiaodong Zhang; Ruilin Su; Ke Pan; Hongbin Liu (Global Change Biology, 2025)
The rise in surface ocean temperature imposes strong effects on marine organisms. With large population sizes and fast generation times, microorganisms may rapidly adapt to ocean warming. However, long‐term experimental adaptation studies on heterotrophic protists are very limited, hindering our comprehensive understanding of their adaptation capability and the underlying mechanisms. In this study, we conducted long‐term thermal selection experiments on six representative marine protozoa. By assessing their phenotypes, metabolism, thermal performance curves, thermal traits, and carbon allocation status, we found that all investigated heterotrophic protists exhibited a fitness‐improved adaptation response to warming scenarios. After growing in warmer conditions for hundreds of generations (~850 for Cafeteria burkhardae and ~500 for other species), their optimal temperature and maximum rates of both growth and ingestion increased, whereas respiration rates significantly decreased. In addition, the cell size, cellular carbon, and nitrogen content at an elevated environmental temperature also increased after warming adaptation. Mechanisms underlying the increased competitive fitness at high temperatures after warming adaptation might be associated with the alleviated oxidative stress, shown by the remarkable reduction in cellular reactive oxygen species contents. Our study, for the first time, reveals the ability of marine heterotrophic protists to adapt to higher temperatures, providing experimental support for predictive modeling studies that integrate evolutionary potential with short‐term physiological responses, with important implications for marine ecosystem functioning and biogeochemical cycling under global warming.

Microplastics magnify inhibitive effects of perfluorooctanoic acid on the marine microbial loop - Peichun Lin; Xiaokun Liu; Zuyuan Gao; Yelinzi Yuan; Hongbin Liu; Lingfeng Huang; Zhili He; Qinglu Zeng; Shanquan Wang (Environmental Research, 2025)

Unlocking the effects of acid/alkali-catalyzed glycerol organosolv pretreatment on lignocellulosic biorefinery: Substrate digestibility and high-quality lignin - Lingfeng Long; Dongqin He; Tao Zhang; Xiaoxiao Chen; Xianzhi Meng; Arthur J. Ragauskas; Chen Huang (Bioresource Technology, 2025)

Tracing offshore marine ecosystem asset changes based on physical accounting: A case of Xiamen Sea Area - Junbo Wang; Benrong Peng; Lingfeng Huang; Keliang Chen (Ocean & Coastal Management, 2024)

Development and application of a low-cost and portable multi-channel spectral detection system for mutton adulteration - Shichang Wang; Binbin Fan; Zhongtao Huang; Zongxiu Bai; Rongguang Zhu; Lingfeng Meng (Biosystems Engineering, 2024)

Paleoclimate evolution of the Middle Triassic Guanling Formation from South China and its significance for the preservation of the Luoping biota - Zhongzhao Ding; Zhixin Ma; Shixue Hu; Shuang Dai; Qiyue Zhang; Xiao Min; Jinyuan Huang; Wen Wen; Changyong Zhou; Xinnan Fang; Tianqi Ji; Lingfeng Qin (Global and Planetary Change, 2024)

Diversification in birds is promoted by plant diversity, topographic heterogeneity and stable paleoclimate - Xinyu Wang; Lu Miao; Xiongwei Huang; Lingfeng Mao; Tianlong Cai; Jens‐Christian Svenning; Gang Feng (Journal of Biogeography, 2024)
Aims Long‐term climate stability, contemporary climate and environmental heterogeneity have been linked to bird diversity patterns through their direct impacts on diversification rate, as well as through their indirect effects on plant species richness, which could also directly and indirectly affect bird diversity. This study aimed to quantitatively assess whether these potential drivers could indirectly affect bird species richness through their direct effects on the diversification rate in birds in eastern Asia. Location Mainland China. Taxon Birds. Methods Using the distribution data of 1127 bird species across 320 prefecture cities in China and a phylogenetic tree of these bird species, we analysed the distribution patterns of bird species richness and diversification rate of all birds, passerine birds and non‐passerine birds, respectively. We also investigated their relationships with long‐term climate stability, contemporary climate, elevation range and plant diversity using ordinary least squares regression model and simultaneous autoregressive model. In addition, structural equation model was used to analyse whether these drivers could indirectly affect bird species richness through their direct effects on bird diversification rate. Results The results showed that bird species richness and diversification rate were highest in southwestern China. Additionally, diversification rate for passerine birds was higher than non‐passerine birds and all birds. Regression analyses revealed that plant species richness was the variable most associated with bird species richness and diversification rate across the three groups. Notably, results from structural equation model indicated that plant species richness, elevation range and glacial–interglacial climate change can indirectly influence bird species richness by directly affecting diversification rates. Main Conclusions These findings emphasize the importance of considering diversification rate when understanding the geographic distribution patterns of bird diversity. The direct and indirect effects of plant species richness, elevation range and glacial–interglacial climate change on bird diversity highlight the crucial role of mountain regions with higher plant diversity and stable paleoclimate in forming and maintaining biodiversity.

Croakers in three coastal areas of Lagos state, Nigeria: Sustainability levels and stakeholders’ perceptions on the use of ecosystem-based fisheries management - Igbodiegwu Gloria Chinwendu; Markus Leibrecht; Okoli Moses Ugochukwu; Obasi Ephraim Uzoma; Lingfeng Huang (Marine Policy, 2024)

Urbanization significantly increases greenhouse gas emissions from a subtropical headwater stream in Southeast China - Mutan Dai; Yuanhui Xu; Yegenberdy Genjebay; Lingfeng Lu; Chuan Wang; Hao Yang; Changchun Huang; Tao Huang (Science of The Total Environment, 2024)

Janus graphene oxide membrane with rational allocation of functional regions as unidirectional ion valve system - Jundong Yan; Lingfeng Liu; Zhichen Liang; Chongfeng Huang; Wenbiao Zheng; Changsheng Guo; Minchao Liu; Chao Peng; Jianbo Jia; Mengchen Zhang (Desalination, 2024)

Unveiling the structure-performance of MoO3/La2O2CO3 for ultra-deep aerobic oxidative desulfurization of diesel - Shijia Shao; Hui Liu; Xiangdong Wang; Lingfeng Jia; Shuhui Zhou; Yan Huang; Huifang Cheng; Feng Liu; Yun Wang; Jixing Liu; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Comparison of the toxic effects of polystyrene and sulfonated polystyrene on wheat under cadmium stress - Lingfeng Qin; Gonghao Liu; Jiaoyan Huang; Zihang Zeng; Ya Zeng; Taiping Qing; Peng Zhang; Bo Feng (Journal of Hazardous Materials, 2024)

FSP1-mediated ferroptosis in cancer: from mechanisms to therapeutic applications - Ran Gao; Jinge Wang; Jingjing Huang; Tong Wang; Lingfeng Guo; Wenlu Liu; Jialu Guan; Desen Liang; Qinghui Meng; Huayang Pan (Apoptosis, 2024)

Doped microspheres for whispering gallery mode microlasing - Xiaoxuan Wang; Chaoyang Huang; Chuansheng Xia; Feifei Qin; Gangyi Zhu; Lingfeng Mao; Yi Ma; Zengliang Shi; Qiannan Cui; Chunxiang Xu (Science Bulletin, 2024)

Hypoxia impairs cellular energy allocation in the juvenile horseshoe crab Tachypleus tridentatus - Lingfeng Jiang; Meilian Huang; Chunhua Liu; Mohamed H. Abo-Raya; Xiaowan Ma; Youji Wang; Menghong Hu (Journal of Experimental Marine Biology and Ecology, 2024)

Impact of hypoxia on glucose metabolism and hypoxia signaling pathways in juvenile horseshoe crabs Tachypleus tridentatus - Lingfeng Jiang; Yueyong Shang; Yuntian Shi; Xiaowan Ma; Malik ShahZaib Khalid; Meilian Huang; James Kar-Hei Fang; Youji Wang; Kianann Tan; Menghong Hu (Marine Environmental Research, 2024)

Responses of microeukaryotic community structure to a Phaeocystis globosa bloom in a semi-enclosed subtropical bay - Beibei Han; Rongjun Shi; Shufei Zhang; Anji Lian; Zexing Kuang; Fengxia Wu; Lingfeng Huang; Honghui Huang (Marine Environmental Research, 2024)

Valorization of straw biomass into lignin bio-ink, bacterial cellulose and activated nanocarbon through the trade-off alkali-catalyzed glycerol organosolv biorefinery - Lingfeng Long; Jinkang Chen; Yueqin Cao; Chen Huang; Shoushuai Feng; Hailin Yang; Dong Tian (Chemical Engineering Journal, 2024)

Growth patterns and optimum habitat of Larimichthys crocea throughout ontogenesis based on a bioenergetics model - Bin Xie; Shin-ichi Ito; Lingfeng Huang; Haiqing Yu; Chenying Guo; Ziqin Wang (Regional Studies in Marine Science, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Wintertime ocean–atmosphere interaction processes associated with the SST variability in the North Pacific subarctic frontal zone - Qionghui Huang; Jiabei Fang; Lingfeng Tao; Xiu-Qun Yang (Climate Dynamics, 2024)
Recent research indicates that the midlatitude oceanic frontal zones are the key regions of ocean–atmosphere interaction. The thermal condition of midlatitude ocean in frontal zones can affect the atmosphere efficiently through both diabatic heating and transient eddy feedback. In this study, the wintertime SST variability in the subarctic frontal zone (SAFZ) of the North Pacific and the associated ocean–atmosphere interaction mechanism are examined based on observational and theoretical analyses. It is found that the SAFZ-related SST anomaly is characterized as a large-scale interannual mode that can persist during the whole winter, and that its evolution is accompanied with local ocean–atmosphere interaction processes. The initial anticyclonic surface wind anomaly associated with the weakened Aleutian Low forces a large-scale warm SST anomaly in midlatitude North Pacific by driving northward Ekman flow and downward heat flux. With the increase of SST anomaly, the air-sea heat flux exchange reverses, indicating that the ocean starts to heat the atmosphere. In addition to increasing the diabatic heating, the warm SST anomaly strengthens the SST gradient in the north part of SAFZ. The low-level atmospheric baroclinicity is adjusted to synchronize with the SAFZ correspondingly due to oceanic thermal influence, causing change of transient eddy activities. Though all the ocean-induced diabatic heating, transient eddy heating and transient eddy vorticity forcing are enhanced over SAFZ, the last physical process plays the most important role in shifting and maintaining the equivalent barotropic atmospheric circulation anomalies. Therefore, the ocean–atmosphere interaction provides a mechanism for the development and maintenance of SAFZ-related anomalies of the North Pacific ocean–atmosphere system throughout the winter.

A bioinspired setup to evaluate food graininess via tactile friction and vibration - Liwen Huang; Chengjin Du; Lingfeng Wang; Chaoyi Yuan; Jun Wang; Dongdong Du (Journal of Food Engineering, 2024)

Molecular docking and antibacterial activity of Sargassum fusiforme extracts against major coral pathogens - Nedaa Ahmed; Mohamed A. M. El-Tabakh; Hala F. Mohamed; Xudong Wu; Changan Xu; Lingfeng Huang (World Journal of Microbiology and Biotechnology, 2023)

Environment drives the co-occurrence of bacteria and microeukaryotes in a typical subtropical bay - Yifan Ma; Lingfeng Huang; Wenjing Zhang (Journal of Oceanology and Limnology, 2023)

Integrated assessment of land-to-river Cd fluxes and riverine Cd loads using SWAT-HM to guide management strategies - Lingfeng Zhou; Miaomiao Teng; Fanhao Song; Xiaoli Zhao; Fengchang Wu; Yaobin Meng; Yuanyi Huang; Karim C. Abbaspour (Journal of Environmental Management, 2023)

Fabrication of immobilized lipases for efficient preparation of 1,3-dioleoyl-2-palmitoylglycerol - Lihong He; Can Zeng; Lingfeng Wei; Li Xu; Fenglin Song; Jianrong Huang; Nanjing Zhong (Food Chemistry, 2023)

Surface display of major capsid protein on Bacillus subtilis spores against largemouth bass virus (LMBV) for oral administration - Quan Wang; Xia Liang; Yunshang Ning; Shijia Liu; Zengjian Liang; Zemiao Zhang; Yingjing Chen; Jinqiao Cao; Fubao Wang; Lingfeng Lan; Guangzhao Cheng; Youhua Huang; et al. (Fish & Shellfish Immunology, 2023)

Water mass-driven multiple ecological effects determine the biodiversity and community assembly of microbial flagellates in subtropic-tropic marginal seas of China - Xin Guo; Qiang Liu; Xiaoqing Lin; Xinyi Zheng; Cheng Huang; Mengwen Pang; Lingfeng Huang (Estuarine, Coastal and Shelf Science, 2023)

Effect of Angiogenesis in Bone Tissue Engineering - Jianhao Huang; Qixiu Han; Meng Cai; Jie Zhu; Lan Li; Lingfeng Yu; Zhen Wang; Gentao Fan; Yan Zhu; Jingwei Lu; Guangxin Zhou (Annals of Biomedical Engineering, 2022)

Ecosystem Services of Ecosystem Approach to Mariculture: Providing an Unprecedented Opportunity for the Reform of China’s Sustainable Aquaculture - Xijie Zhou; Jinghui Fang; Siyuan Shi; Ling Yang; Bin Xie; Lingfeng Huang (Frontiers in Marine Science, 2022)
China is the biggest provider of mariculture products, and the industry is still growing rapidly. Increasing scientific evidence indicates that mariculture may provide valuable ecosystem goods and services in China. Here, we performed a systematic literature review of studies with the aim of understanding the ecosystem services of mariculture and a comprehensive review of ecosystem approaches that may improve mariculture ecosystem services and goods in China. We highlight four ecosystem services functions in China, including food supply, nutrient extraction, carbon sequestration, and biodiversity conservation. Given the further reform of China’s mariculture, we outlined several ecosystem approaches including integrated multi-trophic aquaculture (IMTA), carrying capacity assessment and monitoring, marine spatial planning, and waste treatment and recirculating mariculture system. We conclude that the ecosystem services of the ecosystem approach to mariculture provide an unprecedented opportunity for the reform of China’s sustainable aquaculture. Finally, a synthesis of sustainable development of mariculture, along with the five recommendations for future mariculture development in China, is outlined.

Estimating the Impact of a Seasonal Fishing Moratorium on the East China Sea Ecosystem From 1997 to 2018 - Lingyan Xu; Puqing Song; Yuyu Wang; Bin Xie; Lingfeng Huang; Yuan Li; Xinqing Zheng; Longshan Lin (Frontiers in Marine Science, 2022)
Fisheries management policies (FMPs) have been implemented in coastal countries to ensure a sustainable supply of seafood and the recovery of species diversity. Because of the depletion of fishery stocks, China has introduced a series of FMPs since 1995, including a seasonal fishing moratorium (SFM), a zero-growth strategy, and a minimum mesh size for fishing nets. Here, we built two mass balance models for 1997–2000 (M1997) and 2018–2019 (M2018) using Ecopath with Ecosim 6.6 to illustrate the interannual changes over the past two decades in the East China Sea (ECS). We then simulated two dynamic scenarios from 1997 to 2018, SFM (M2018 SFM ) and no SFM (M2018 no-SFM ), to test the role of the SFM under fishing pressure in the ECS. Ecopath showed that the ECS ecosystem is becoming more mature, although it is still unstable, featuring lower total primary production/total respiration, longer cycles, faster organic material circulation speed, and a higher omnivorous degree. This suggests a slow recovery for the ECS ecosystem in the past two decades. The biomass of fish in the ECS—especially the planktivores, dominated by small-sized Benthosema pterotum —significantly increased in M2018 versus M1997, but there were fewer medium- and large-sized fish. The keystone species switched from the planktivores/piscivores dominated by Decapterus maruadsi in M1997 to planktivores in M2018. Ecosim illustrated that the SFM has positive effects on fishery resources recovery, especially for commercial fishes (i.e., large yellow croakers and hairtails), as reflected by the significantly higher predicted biomass of fish in M2018 SFM compared to M2018 no-SFM and M1997, although the bioaccumulation was consumed by the intense fishing pressure after the SFM. However, the M2018 SFM prediction for nektons was still lower than the actual value, especially for planktivores, which display a sharp increase in biomass. This should be partly attributable to the policy of the minimum mesh size (<5 cm was banned), which benefits B. pterotum due to its 3.5 cm maximum body size. Therefore, a series of FMPs, rather than only the SFM, functioned together in the ECS ecosystem. However, the mixed trophic impact indicated a negative impact if the fisheries were further developed. Fishery management in the ECS needs to be strengthened by extending the SFM and reducing fishing pressure after the SFM.

A novel surface sterilization method using Artemisia dracunculus extract for tissue culturing of endangered species Sargassum fusiforme - Nedaa Ahmed; Hala F. Mohamed; Changan Xu; Xihuang Lin; Lingfeng Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Using Stakeholders’ Perception to Evaluate the Prospects of Establishing Marine Protected Areas in the Niger Delta Coastal Ecosystem - Ebuka Benedict Okeke; Somadina Mmaduakonam Obodoefuna; Mohammad Mazbah Uddin; Lingfeng Huang (Coastal Management, 2022)

Determination of trophic levels of marine fish in the Yellow Sea and northern East China Sea using nitrogen stable isotope (δ15N) analysis of otoliths - Huaiyu Bai; Yukun Wang; Tingting Zhang; Fangqun Dai; Lingfeng Huang; Yao Sun (Journal of Oceanology and Limnology, 2022)

Seasonal and Spatial Variation of Pelagic Microbial Food Web Structure in a Semi-Enclosed Temperate Bay - Haibo Li; Xue Chen; Michel Denis; Yuan Zhao; Lingfeng Huang; Zengjie Jiang; Wuchang Zhang; Tian Xiao (Frontiers in Marine Science, 2020)

Grazing by microzooplankton and copepods on the microbial food web in spring in the southern Yellow Sea, China - Yuan Zhao; Yi Dong; Haibo Li; Shiquan Lin; Lingfeng Huang; Tian Xiao; Gerald Gregori; Li Zhao; Wuchang Zhang (Marine Life Science & Technology, 2020)
Assessment of microzooplankton and copepods grazing pressure on picoplankton is a key requirement for resolving the microbial food web efficiency. Although microzooplankton grazing on picoplankton has been extensively studied, the impact of microzooplankton on different groups of picoplankton, i.e., heterotrophic bacteria, Synechococcus and picoeukaryotes have rarely been compared. Furthermore, in the very few existing studies there is no consistent evidence of an enhancing or restraining effect of copepods on picoplankton. More studies are needed to improve our understanding of the influence of microzooplankton and copepod on picoplankton. Dilution incubations and copepod addition incubations were performed during a cruise to the southern Yellow Sea on May 16–29, 2007. The bulk grazing of microzooplankton and the calanoid copepod Calanus sinicus on phytoplankton, flagellates and picoplankton was estimated. Stations were divided into either eutrophic or oligotrophic according to the nutrient and biological parameters. Picoplankton comprised a large part of the diet of microzooplankton in the central oligotrophic area, while phytoplankton was the main food of microzooplankton in the coastal eutrophic area. In the central oligotrophic area, microzooplankton preferred grazing on Synechococcus . After copepod addition, ciliate abundance decreased while Synechococcus abundance increased (382%, 64% and 64% at three experimental stations, respectively), indicating strong grazing pressure of microzooplankton on Synechococcus . Our results suggest that Synechococcus might be an essential carbon source the planktonic food web in the oligotrophic waters of southern Yellow Sea.

Mechanism test on inhomogeneity of dredged fill during vacuum preloading consolidation - Yingguang Fang; Lingfeng Guo; Junwen Huang (Marine Georesources & Geotechnology, 2019)

Spatiotemporal variation in environmental features and elemental/isotopic composition of organic matter sources and primary producers in the Yundang Lagoon (Xiamen, China) - Xinqing Zheng; Serena Como; Paolo Magni; Lingfeng Huang (Environmental Science and Pollution Research, 2019)

Amphipods fail to suppress the accumulation of Ulva lactuca biomass in eutrophic Yundang Lagoon - Xinqing Zheng; Lingfeng Huang; Qian Wang; Rongcheng Lin (Acta Oceanologica Sinica, 2014)

Weak coupling between heterotrophic nanoflagellates and bacteria in the Yellow Sea Cold Water Mass area - Shiquan Lin; Lingfeng Huang; Jiachang Lu (Acta Oceanologica Sinica, 2014)

Factors regulating population dynamics of the amphipod Ampithoe valida in a eutrophic subtropical coastal lagoon - Xinqing Zheng; Lingfeng Huang; Bangqin Huang; Yongqing Lin (Acta Oceanologica Sinica, 2013)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

Multiparameter cluster analysis of seasonal variation of water masses in the eastern Beibu Gulf - Shengli Chen; Yan Li; Jianyu Hu; Airong Zheng; Lingfeng Huang; Yuanshao Lin (Journal of Oceanography, 2011)

The treatment of chlorophenols with laccase immobilized on sol–gel-derived silica - Lingfeng Qiu; Zhixin Huang (World Journal of Microbiology and Biotechnology, 2010)

Spatial and temporal distribution of nanoflagellates in the northern South China Sea - Bangqin Huang; Wenlu Lan; Zhenrui Cao; Minhan Dai; Lingfeng Huang; Nianzhi Jiao; Huasheng Hong (Hydrobiologia, 2008)